The influence of socio-demographic and environmental factors on the fall rate in geriatric patients in primary health care - Kamińska, Magdalena Sylwia; Brodowski, Jacek; Karakiewicz, Beata (Family Medicine & Primary Care Review, 2017)
Background . A fall is defined as an event which results in a person coming to rest inadvertently on the ground or floor or other lower level. Falls are the leading cause of injuries among geriatrics and a factor which significantly lowers their quality of life. Objectives. The aim of this study was to identify fall risk factors in the elderly with regard to their environmental situation and sociodemographic data. Material and methods. This epidemiological population-based study involved 304 patients from selected outpatient clinics. The median age was 79 years. Our study employed a diagnostic survey-based method using an environmental inquiry of our devising, as well as the Tinetti Test (TT). Results . A statistically significant correlation was found between the number of falls and such variables as age, the family structure and family care efficiency (p 0.05). Regardless of whether the respondents experienced falls or not, a vast majority of them showed a need for information support concerning the reduction of fall risk in the future. Conclusions . 1. Risk factors for falls among geriatric patients include age, falls in the medical history, solitude as an adverse social situation and the unpreparedness of the family for taking non-professional care of their elderly relatives. 2. According to the respondents, information support may improve their knowledge of fall prevention and ways of handling the situation with increasingly limited self- -reliance, and the preparation of their families for taking care of them may reduce the risk of falls.